Pengaruh Intellectual Capital Dan Leverage Terhadap Financial Performance Dengan Moderasi Firm Size - Henny Wirianata, Viriany, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to obtain empirical evidence in regard to the effect of intellectual capital, leverage, and liquidity on financial performance, with firm size as a moderating variable on companies in manufacturing sector, listed in Indonesia Stock Exchange for the 2017-2019 period. The research data was tested by utilizing Eviews version 11. The research samples that used are 64 companies in manufacturing sector with a total of 192 data sorted by utilizing purposive sampling technique. The research results indicate that intellectual capital possess a positive and significant effect on financial performance, while leverage possess insignificant effect on financial performance. Furthermore, the results also indicate that firm size moderate the effect of intellectual capital and leverage on financial performance.